2018
DOI: 10.1016/j.ebiom.2018.09.046
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin-producing hepatocellular A7 triggering ovulation indicates a potential beneficial role for polycystic ovary syndrome

Abstract: BackgroundThe ovulatory dysfunction mechanisms underlying polycystic ovary syndrome (PCOS) are not completely understood. And the roles of EPHA7 and EPHA7-regulated pathway factors in the pathogenesis of anovulation remain to be elucidated.MethodsWe used human granulosa cells (hGCs) of PCOS and non-PCOS patients to measure EPHA7 and other target gene expressions. We performed in vitro experiments in KGN cells to verify the molecular mechanisms. Additionally, we conducted in vivo loss- and gain-of-function stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 68 publications
(94 reference statements)
3
13
0
Order By: Relevance
“…Indeed, after 1 week of modelling followed by superovulation, FHL2 overexpression rats displayed significantly decreased ovulation efficiency and MII oocyte rate. Following 3 weeks of modelling, we detected that FHL2 overexpression group displayed acyclicity and PCOM, which were similar to the phenotypes of PCOS rat models observed previously in our laboratory [19,68]. All of these clues indicate that FHL2 may play a role in the development of the ovarian features of PCOS.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Indeed, after 1 week of modelling followed by superovulation, FHL2 overexpression rats displayed significantly decreased ovulation efficiency and MII oocyte rate. Following 3 weeks of modelling, we detected that FHL2 overexpression group displayed acyclicity and PCOM, which were similar to the phenotypes of PCOS rat models observed previously in our laboratory [19,68]. All of these clues indicate that FHL2 may play a role in the development of the ovarian features of PCOS.…”
Section: Discussionsupporting
confidence: 87%
“…Among these regulatory genes, four and a half LIM domain (FHL) 1 and 2 as well as C/EBPb were identified based on the high frequencies of their occurrence in the gene expression profiles. C/EBPb is an essential ERK1/2-mediated ovulation-related gene [15], and its lower expression in hGCs from patients with PCOS that involved in the pathogenesis of ovulatory dysfunction of PCOS has been demonstrated by our research group [19]. Therefore, we hypothesised that FHL1/2 plays a role in the development of PCOS and we examined whether FHL1/2 can regulate ovulation-related genes related to ovulatory disorder in PCOS.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Predominant proestrus stage was observed in the curcumin treated group whereas estrus phase was observed as the predominant phase (35.6±1.5) in the groups treated with nanoparticles. Previous research studies 77 , 78 also reported similar effects on the estrous cycle with different suggested protocol.…”
Section: Resultssupporting
confidence: 61%
“…Unlike miRNA mimics, siRNAs and shRNAs exhibit higher specificity by binding specifically the targeted mRNA. siRNAs against EphA4 have been used to highlight the negative role of EphA4 in recovery after brain hemorrhages [104] while an shRNA against EphA7 was employed to demonstrate its implication in the ovulation process [105]. Despite their common higher specificity, siRNAs and shRNAs present several differences (for review see [106]).…”
Section: Interfering Rnasmentioning
confidence: 99%